An approach to shortening the timeframe between the emergence of new compounds on the drugs market and the availability of reference standards: The microscale syntheses of nitrazolam and clonazolam for use as reference materials, utilizing polymer‐supported reagents. Issue 7 (24th April 2018) - Dowling, Geraldine; Kavanagh, Pierce V.; Eckhardt, Hans‐Georg; Twamley, Brendan; Hessman, Gary; McLaughlin, Gavin; O'Brien, John; Brandt, Simon D.
Abstract: Nitrazolam and clonazolam are 2 designer benzodiazepines available from Internet retailers. There is growing evidence suggesting that such compounds have the potential to cause severe adverse events. Information about tolerability in humans is scarce but typically, low doses can be difficult to administer for users when handling bulk material. Variability of the active ingredient in tablet formulations can also be of a concern. Customs, toxicology and forensic laboratories are increasingly encountering designer benzodiazepines, both in tablet and powdered form. The unavailability of reference standards can impact on the ability to identify these compounds. Therefore, the need arises for exploring in‐house approaches to the preparation of new psychoactive substances (NPS) that can be carried out in a timely manner. The present study was triggered when samples of clonazolam were received in powdered and tablet form at a time when reference material for this drug was commercially unavailable. Therefore, microscale syntheses of clonazolam and its deschloro analog nitrazolam were developed utilizing polymer‐supported reagents starting from 2‐amino‐2'‐chloro‐5‐nitrobenzophenone (clonazolam) and 2‐amino‐5‐nitrobenzophenone (nitrazolam). The final reaction step forming the 1, 2, 4‐triazole ring moiety was performed within a gas chromatography–mass spectrometry (GC–MS) injector. A comparison with a preparative scale synthesis of both benzodiazepine derivatives showed that microscale synthesis might be an attractive option for a forensic laboratory in terms of time and cost savings when compared with traditional methods of synthesis and when qualitative identifications are needed to direct forensic casework. The reaction by‐product profiles for both the micro and the preparative scale syntheses are also presented. Abstract : The microscale syntheses of clonazolam and nitrazolam were developed utilizing polymer‐supported reagents starting from 2‐amino‐2'‐chloro‐5‐nitrobenzophenone and 2‐amino‐5‐nitrobenzophenone respectively. The final reaction step forming the 1, 2, 4‐triazole ring moiety was performed within the GC‐MS injector. A comparison with preparative scale syntheses of both benzodiazepine derivatives showed that microscale synthesis may be an attractive option for a forensic laboratory in terms of time and cost savings when compared with traditional synthetic methods and when qualitative identifications are needed to direct forensic casework.